133k views
3 votes
Use the properties of logarithms and the values below to find the logarithm indicated.

Use the properties of logarithms and the values below to find the logarithm indicated-example-1
User Dusan
by
5.7k points

2 Answers

4 votes

Answer:

-2B

Explanation:

log₉ (1/16)

log₉ (16^-1)

log₉ (4^-2)

Using exponent property of logs:

-2 log₉ (4)

Substituting:

-2B

User Kamalakshi
by
5.8k points
5 votes

Answer:

-2B

(I guess this is what you are looking for; didn't need A or C).

Explanation:

It seems like to wants us to to find
\log_9((1)/(16)) in terms of
A,B,C.

First thing I'm going to do is rewrite
\log_9((1)/(16)) using the quotient rule.

The quotient rule says:


\log_m((a)/(b))=\log_m(a)-\log_m(b)

So that means for our expression we have:


\log_9((1)/(16))=\log_9(1)-\log_9(16)

Second thing I'm going to do is say that
\log_9(1)=0 \text{ since } 9^0=1.


\log_9((1)/(16))=\log_9(1)-\log_9(16)


\log_9((1)/(16))=-\log_9(16)

Now I know 16 is 4 squared so the third thing I'm going to do is replace 16 with 4^2 with aim to use power rule.


\log_9((1)/(16))=\log_9(1)-\log_9(16)


\log_9((1)/(16))=-\log_9(16)


\log_9((1)/(16))=-\log_9(4^2)

The fourth thing I'm going to is apply the power rule. The power rule say
\log_a(b^x)=x\log_a(b). So I'm applying that now:


\log_9((1)/(16))=\log_9(1)-\log_9(16)


\log_9((1)/(16))=-\log_9(16)


\log_9((1)/(16))=-2\log_9(4)

So we are given that
\log_9(4) is
B. So this is the last thing I'm going to do is apply that substitution:


\log_9((1)/(16))=\log_9(1)-\log_9(16)


\log_9((1)/(16))=-\log_9(16)


\log_9((1)/(16))=-2\log_9(4)


\log_9((1)/(16))=-2B

User Johannes
by
6.3k points